Traffic medicine in Saudi Arabia, from prevention to rehabilitation - Saud Al Turki (19807254) (2015)
Saudi Arabia is a vast country of 2,149,690 km2, and is the largest Arab state in Western Asia. The Kingdom has been categorized as a high-income nation, and is part of the “Group of Twenty” (G-20) of major economies. It has a total population of approximately 27 million, one-fourth of whom are expatriates, with the highest population density (per km2) of 101 in Jizan, and 38 in Makkah, and the lowest of 2.8 in Najran, and 3.6 in Al Jawf. In KSA, motor vehicles are the main means of transportation within, and in-between cities. According to a recent estimate, more than 6 million cars are found on the roads of KSA. According to the morbidity and mortality records in the Ministry of Health (MOH) hospitals, 20% of beds are occupied by RTA victims, and 81% of deaths in the hospitals are due to RTIs. Over the past 2 decades, KSA has recorded 86,000 deaths, and 611,000 injuries in RTAs with 7% resulting in permanent disabilities. Road traffic accidents are a major health hazard with 19 killed daily, and 4 injured every hour in KSA. Al Naami et al, in his article mentioned the common reasons behind the soaring numbers of road traffic accidents in Saudi Arabia, which included the human factor, the vehicle, and the road/environment (2). Among the human factor, Driver errors account for about 80% of all RTAs in Saudi Arabia. Overspeeding is responsible for 65% of all traffic accidents (3.5 times the incidence in the USA). Violation of traffic signals at urban intersections is responsible for about 50% of accidents (4.5 times more common than in the USA). Vehicles and road layouts contribute to accidents and account for 20% of RTAs in Saudi Arabia, Tire blowouts and poor roads are very “hot” safety issues in Saudi Arabia, particularly in rural areas. Environmental factors such as rain, fog, and dust have minimal effects on RTAs in Saudi Arabia. However, extreme heat is responsible for 39% of all accidents due to tire blowouts. Heat also contributes to driver stress levels, leading to reduced mental capacity. Traffic medicine in Saudi Arabia has focused more on the prevention approach rather than the rehabilitation, The evidence sufficiently supports that the action plans in KSA so far have mostly focused on the prevention of RTIs rather than RTAs, including seat belt laws, Saher system, emergency medical rescue services, and the role of the police in the documentation of RTAs. While the international recommendations emphasize on developing institutional framework, safer roads and vehicles, proper surveillance or data system, safer road users, and post-crash care. The MOH in collaboration with the Ministry of Interior launched a road safety program called Saher in 2009. It is an automated system that was developed to manage traffic via electronic systems in major cities in Saudi Arabia, this newly established system uses a digital camera network connected to the national information center to track any violations and to control traffic. However, data on its long term effects on accidents and death are not yet available(3). Another important aspect of traffic medicine is the implementation of Trauma Registry as part of the national trauma system project, trauma registries can provide information on injury pattern and allow statistical modeling of trauma related variables to identify public health threats and prioritize interventions. Additionally registries can help monitor the epidemiology of serious injuries, track hospital performance overtime, and benchmark outcomes between hospitals and regions(4). Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.97